VALUE RELEVANCE DAN IFRS ADOPTION DI INDONESIA: INVESTIGASI PADA PERUSAHAAN LQ-45 BURSA EFEK INDONESIA - Triandi ,; Suratno ,; Nurmala Ahmar (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2015)
Value relevance is being defined as the ability of information disclosed by financial statements to capture and summarize firm value. earnings per share (EPS) and book value of shares (BVS) and stock market price (SMP), both before and after IFRS adoption. Based on theresult,test there the valuerelevancebefore and after IFRS adoptio. The value relevance after IFRS adoption decreased. These findings differ from the findings in several countries have adopted IFRS. In many countries have adopted IFRS tends to increase the value relevance.Keyword : value relevance, earning per share, book value of equity, stock price, IFRS adoption, LQ-45